Genesis by the Numbers: a reassessment of the years of the patriarchs, beginning with the Joseph story - Driver, Daniel R. (Journal of the bible and its reception, 2019)
Do the numbers of years in Genesis add up? Biblical scholars have learned to attend to the art of biblical narrative. Is there also an art of biblical numbers? If so, could its rediscovery lead to a better understanding of the contours of the biblical text, and its complex meanings, as well as its reception history prior to the Enlightenment? This article’s provisional answer to these questions is yes. It looks at two key numbers associated with the Joseph Story: a span of twenty-two years, which a variety of readers calculate as the time that Joseph lived away from his family in Egypt; and a double span of seventeen years, which the Bible suggests is the length of time that Joseph lived under his father’s protection in Canaan, and that Jacob in turn lived under his son’s care in Egypt. The study finds that, since Spinoza, modern assessments of these numbers have been constrained by a strongly linear view of time, as may be seen in the work of Robert Alter, among many others. It criticizes linear time as reductive insofar as it flattens the numbers of Genesis into chronologies and timelines. It also draws attention to an aspect of figural time, which it describes as symmetrically folded time, to help characterize the non-linear, isotropic way that numbers seem to behave in the Bible and in the Bible’s pre-modern reception. The findings about figural time in the Joseph Story raise significant questions about the compatibility of narrative, literary-critical, and theological approaches to the time-denominated numbers of Genesis.